Utilization of Geospatial Technology and WebGIS in Disaster Risk Analysis of Mount Merapi Lava Flow - Ananda Rianti Dewi; Didik Taryana (CV Bumi Spasial, 2026)
While Mount Merapi's high eruptive activity poses severe rain lahar threats, there remains a critical gap in integrating comprehensive spatial risk assessments into accessible geo-education frameworks. This study addresses this void by evaluating the risk levels of rain lahar disasters to support spatial-based mitigation learning. The high activity of Mount Merapi has various potential eruption hazards, one of which is the danger of lava flows that can occur at any time and threaten the safety of the surrounding community. Therefore, this study aims to examine the level of risk of lava flow disasters on Mount Merapi. The spatial data and WebGIS platform generated from this study are specifically designed to enhance students' geospatial literacy and formulate place-based disaster preparedness education for local communities in high-risk zones. This research employs a quantitative spatial modeling approach utilizing Weighted Overlay Analysis and Spatial Multi-Criteria Evaluation (SMCE) within a Geographic Information Systems (GIS) framework. The data used is in the form of secondary data collected through literature study activities on various sources. Data processing techniques are used, namely remote sensing and geographic information systems, while in data analysis, risk calculation equations are used according to the Head of BNPB Regulation Number 2 of 2012. Based on the results of the study, it is known that the risk level of lava flow disasters is high in Srumbung District, Muntilan District, and Salam District. Efforts that can be made to respond to the high level of risk are to reduce the level of vulnerability through improving health facilities, education, evacuation, economic guarantees and mitigation systems; and increasing capacity through optimizing cooperation and coordination between parties.